ANALYSIS OF EXCHANGE RATE PASS-THROUGH TO PRICE STABILITY IN INDONESIA 2010-2019 - Annaba Maharani; Hery Sulistio Jati Nugroho Sriwiyanto; Faiza Husnayeni Nahar (Journal of Applied Economics in Developing Countries, 2022)
As an open country, the exchange rate affects Indonesia's macroeconomic stability, especially inflation. Extreme exchange rate depreciation can cause inflation to be high so it disrupts the ultimate goal of monetary policy, namely maintaining price stability. This study identifies the effect of the exchange rate on price stability and the transmission of the exchange rate to price stability. This study uses secondary data on the Nominal Effective Exchange Rate (NEER), Consumer Price Index (CPI), Output Gap, Import Prices, and Oil Prices. The period used is 2010-2019 as quarterly data. The method that will be used in this research is VECM which will look at impulse response and variance decomposition, looking at the long-term effect of variable shocks. The results of this study indicate that shock on the exchange rate affects price stability with direct pass-through between the exchange rate variable and the consumer price index. Recommendations for a good exchange rate policy will also result in a good price stability, this is shown by the consumer price index.